Effect of initial antiretroviral regime on virological suppression in children in a Southern African urban population: a retrospective record review - Gaibee, Zeenaat (Department of Paediatrics and Child Health, 2020)
Background Since 2010, adult studies and clinical concerns about stavudine (d4T) toxicity had led to the phasing out of d4T from many antiretroviral treatment (ART) guidelines globally with substitution by abacavir. Recent studies, within Southern Africa, however have shown poorer virological suppression with abacavir (ABC) compared to d4T at their respective centres. Methods A retrospective study of HIV-positive children, who had been initiated on ART from 2005 to 2017, was conducted at an ART unit at New Somerset hospital, Western Cape, South Africa. Data was extracted from clinical notes and electronic medical records and virological suppression reviewed in those started on ABC and d4T based regimes. Results A total of 672 children were included in the study with a median age of 8.9 months (interquartile range (IQR) 4.1- 24.1 months) in the d4T based group and 11 months (IQR 3.5 - 29.9 months) in the ABC group. 64 of the 437 patients in the d4T containing group were transferred out, 15 reported to have died, and 49 were lost to follow up within the first 6months on treatment. Of the 181 ABC containing regimen group, 1 was transferred out to another care facility, 1 reported death within 6months of treatment and 2 children were lost to follow up. There was a noted increased risk of being virologically unsuppressed at 6months while taking ABC containing regimen compared to a d4T containing regimen. . The relative risk of being virologically unsuppressed at 6 months while taking abacavir/lopinavir (LPV/r) was 1.39 (95% confidence interval 1.03 to 1.88, p=0.04) compared to stavudine/LPV/r. The relative risk of being virologically unsuppressed at 6 months while taking abacavir/efavirenz (EFV) was 1.82 (95% confidence interval 0.98 to 3.37, p=0.054) compared to stavudine/EFV. Conclusion Our analysis again raises concerns about virological suppression in the abacavir era of paediatric ART, compared to the previous stavudine era, particularly in combination with LPV/r in the younger, more vulnerable children. Whether this is because of intrinsic properties of the different medications or is a marker of the evolving complexity of the South African ART rollout, may never be resolved. However, this is of concern as abacavir and LPV/r appear to be entrenched as first-line paediatric ART in a setting where attrition is high, many children are lost to follow up and virologic surveillance is not always optimal. Clinicians need to optimize retention strategies, especially of young infants, to ensure that children are retained in care, have viral load testing timeously, so that those virologically unsuppressed can be detected and treated early and appropriately.